Dari Offline ke Online: Transformasi Penjualan UMKM Magelang dengan Kekuatan Konten Digital - Yusuf Wahyu Setiya Putra; Cisilia Sundari; Mira Fitriana; Kanafi Kanafi; Dwi Astuti; Kapti Kapti; Riska Dwi Handayani (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
This community service aims to empower Micro, Small, and Medium Enterprises (MSMEs) in Magelang in adapting sales models from offline to online through the use of digital content. This activity is motivated by the challenges of MSMEs in expanding market reach and increasing competitiveness in the digital era. The implementation method includes socialization, training in creating attractive and effective digital content, assistance in building an online presence through various platforms, and evaluating the impact of implementing digital content strategies on increasing sales and visibility of MSMEs. The results show a significant increase in the understanding and skills of MSMEs in utilizing digital content for marketing and selling their products. In addition, there was an increase in market reach and potential sales growth for the MSMEs involved. This community service activity concluded that intensive assistance in creating and managing digital content has a crucial role in transforming the MSME sales model from offline to online, thereby increasing competitiveness and business sustainability in the digital era.